Size‐Dependent Cytotoxicity of Monodisperse Silica Nanoparticles in Human Endothelial Cells - Napierska, Dorota; Thomassen, Leen C. J.; Rabolli, Virginie; Lison, Dominique; Gonzalez, Laetitia; Kirsch‐Volders, Micheline; Martens, Johan A.; Hoet, Peter H. (Small (Weinheim an der Bergstrasse, Germany), 2009)
The effect that monodisperse amorphous spherical silica particles of different sizes have on the viability of endothelial cells (EAHY926 cell line) is investigated. The results indicate that exposure to silica nanoparticles causes cytotoxic damage (as indicated by lactate dehydrogenase (LDH) release) and a decrease in cell survival (as determined by the tetrazolium reduction, MTT, assay) in the EAHY926 cell line in a dose‐related manner. Concentrations leading to a 50% reduction in cell viability (TC50) for the smallest particles tested (14‐, 15‐, and 16‐nm diameter) ranging from 33 to 47 µg cm−2 of cell culture differ significantly from values assessed for the bigger nanoparticles: 89 and 254 µg cm−2 (diameter of 19 and 60 nm, respectively). Two fine silica particles with diameters of 104 and 335 nm show very low cytotoxic response compared to nanometer‐sized particles with TC50 values of 1095 and 1087 µg cm−2, respectively. The smaller particles also appear to affect the exposed cells faster with cell death (by necrosis) being observed within just a few hours. The surface area of the tested particles is an important parameter in determining the toxicity of monodisperse amorphous silica nanoparticles. The cytotoxicity of monodisperse amorphous silica particles of the same morphology and shape but different size is examined in human endothelial cells (EAHY926 cell line). The results indicate that, in human endothelial cells, exposure to silica nanoparticles causes cytotoxic damage (as determined by the tetrazolium reduction and lactate dehydrogenase assays) in a dose‐ and size‐related manner (see image).